Escape rooms and breakouts: Novel educational strategies - Jadán-Guerrero, Janio (2022)
The escape rooms and breakouts are immersive games in which the participants are locked in a room and must solve a series of puzzles to escape. In virtuality, these games have also aroused interest in the educational field as a learning tool to transform students from passive spectators to active participants. Immersive learning allows students to learn about a topic while practicing teamwork and communication. This chapter aims to explain how these tools work and describe the implementation process using digital educational resources available on the web. Some examples developed by the authors are mentioned, and the evaluation results concerning the students' motivation, satisfaction, and participation in a virtual environment are presented.